Pengujian Aplikasi Absensi Karyawan Berbasis Web Menggunakan Standar ISO/IEC 29199 (Studi Kasus: PT Wahana Insan Nugraha) - Ahmad Arisyi; Alif Fullah; Chairul Anwar (CV. Multi Kreasi Media, 2025)
The rapid development of information technology encourages companies to implement web-based employee attendance information systems to improve the efficiency of attendance recording and data management. This study aims to evaluate the functionality and reliability of the employee attendance system at PT Wahana Insan Nugraha using Black box Testing based on the ISO/IEC/IEEE 29119 standard. Testing was conducted on modules including authentication, attendance recording, employee and admin data management, and attendance report presentation. The results indicate that most core functions operate according to specifications; however, bugs were found in the employee data addition feature and sidebar navigation, affecting workflow consistency and user experience. Based on these findings, it is recommended to fix the bugs, conduct further testing, and develop additional features to enhance the system’s stability, reliability, and overall usability.